2010
DOI: 10.1007/s00774-010-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of vitamin E isomer supplementation on static and dynamic bone histomorphometry parameters in normal male rats

Abstract: Bone is a specialized connective tissue that functions as the load-bearing structure of the body. Free radicals may affect bone remodeling by regulating osteoclast activity in either the physiological or pathological condition. Vitamin E, a lipid-soluble antioxidant, has been demonstrated to offer protection against osteoporosis and to improve the bone material and structure of animal models. The aim of this study was to observe and compare the effects of alpha-tocopherol (alpha-tocopherol), delta-tocotrienol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 30 publications
3
72
0
2
Order By: Relevance
“…Some studies suggest that alpha-tocopherol may improve bone quality and strength, (71,72) maintain BMD, (73) decrease bone resorption, (74) and increase bone formation. (75) Hypothesized mechanisms include preventing the accumulation of bone resorbing cytokines, (76) reducing the number of osteoclasts, (75) and increasing the number of osteoblasts. (75) Conversely, other studies suggest that alpha-tocopherol supplementation did not improve bone quality, BMD, or BTMs, (77,78) and in fact one study suggests that a high dose of vitamin E may have a detrimental effect on bone quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that alpha-tocopherol may improve bone quality and strength, (71,72) maintain BMD, (73) decrease bone resorption, (74) and increase bone formation. (75) Hypothesized mechanisms include preventing the accumulation of bone resorbing cytokines, (76) reducing the number of osteoclasts, (75) and increasing the number of osteoblasts. (75) Conversely, other studies suggest that alpha-tocopherol supplementation did not improve bone quality, BMD, or BTMs, (77,78) and in fact one study suggests that a high dose of vitamin E may have a detrimental effect on bone quality.…”
Section: Discussionmentioning
confidence: 99%
“…(75) Hypothesized mechanisms include preventing the accumulation of bone resorbing cytokines, (76) reducing the number of osteoclasts, (75) and increasing the number of osteoblasts. (75) Conversely, other studies suggest that alpha-tocopherol supplementation did not improve bone quality, BMD, or BTMs, (77,78) and in fact one study suggests that a high dose of vitamin E may have a detrimental effect on bone quality. (77) The hypothesized mechanisms for the negative and null effects of alphatocopherol on bone include the excessive suppression of local mediators, which may reduce osteoblastic activity and bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Tocotrienols differ from the tocopherols in that they contain three double bonds in the side chain [12]. In previous studies, tocotrienols have been shown to have better bone protective effects when compared to -tocopherol in animal osteoporosis models [13][14][15][16][17][18][19]. Furthermore, studies also showed that tocotrienols were able to prevent and even reverse osteoporosis in estrogen deficiency, testosterone deficiency, glucocorticoid excess, and nicotine exposure [15][16][17][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In general, sLS/BS parameter corresponds to poor bone formation while dLS/BS, MS/BS and MAR correspond to bone formation and mineralization. A vast amount of literature showed that the use of the Weibel technique is a very effective stereological test system and give reliable results on the analysis of bone static and dynamic histomorphometric parameters (Nazrun et al 2005;Shuid et al 2007;Hermizi et al 2009;Mehat et al 2010;Hermizi et al 2011;Aktifanus et al 2012;Fathilah et al 2012;Hussan et al 2012;Muhammad et al 2012;Soelaiman et al 2012;Abdul-Majeed et al 2012;Chin et al 2014;Parvaneh et al 2015). However, a detailed description of the protocol had not been mentioned.…”
Section: Quantification Of Bone Cellular Histomorphometry Using Weibementioning
confidence: 99%
“…Moreover, these studies used this technique to investigate the efficacy of antiosteoporotic therapies (Nazrun et al 2005;Shuid et al 2007;Hermizi et al 2009;Mehat et al 2010;Hermizi et al 2011;Aktifanus et al 2012;Fathilah et al 2012;Hussan et al 2012;Muhammad et al 2012;Abdul-Majeed et al 2012;Chin et al 2014;Parvaneh et al 2015). These studies have referred to (Weibel et al 1966;Freere & Weibel 1967) in performing the protocol without a detailed description on how did they evaluate the parameters.…”
mentioning
confidence: 99%